ANALISIS KARAKTERISTIK GAYA BELAJAR SISWA BERPRESTASI TERHADAP PRESTASI AKADEMIK DI UPTD SDN PEJAGAN 1 - Desvia Nur Afrida; Nova Elisa Lestari; Putri Aulia Ningtias; Izzah Fijriyah; Ita Indriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify the learning styles of high-achieving students and the factors that support their academic success at UPTD SDN Pejagan 1. The focus of the research is directed toward understanding how learning style, motivation, time management, and environmental support contribute to students’ academic achievement. This study employs a qualitative approach with a descriptive method. Data were collected through interviews with high-achieving students and classroom teachers, as well as observations conducted during the learning process. The results show that high-achieving students tend to have a visual-kinesthetic learning style, meaning they learn best through observation, colors, images, videos, and hands-on activities. The use of this learning style helps students better understand the material, stay active in class, and maintain high concentration. In addition, strong learning motivation both intrinsic and extrinsic serves as the main driving factor behind their success. Support from teachers and parents also has a positive impact on students’ enthusiasm for learning and discipline. Moreover, effective time management enables these students to balance academic and non-academic activities efficiently.It can be concluded that the success of high achieving students results from the interaction between suitable learning styles, high learning motivation, good time management, and social support from both school and family environments. The implication of this study emphasizes the importance of teachers recognizing students’ learning styles in order to design effective, engaging, and student-centered learning strategies